The Effect of Motivation on Work Productivity of Kitchen Employees at Mandarin Oriental Hotel Jakarta - Marya Yenny; Rezka Aida Patriasti Seja Purnama Ningsih; Yanti Suzana; Dendy Nurwenda; Steven Sugiarto (The Postgraduate School of Tourism Sahid Polytechnic, 2023)
Purpose: This study aimed to determine the effect of motivation on employee work productivity. The research was conducted at the Mandarin Oriental Hotel Jakarta to find out how much influence the motivation program has on the work productivity of kitchen employees at the mandarin oriental Jakarta.Research methods: This research uses the type of associative analysis. The method used in this research is quantitative. The sampling technique used in this research is total sampling, in which all population members are employed entirely. Result and discussion: Providing motivation and work productivity of kitchen employees at the Mandarin Oriental Hotel Jakarta with a correlation coefficient shows that explaining ing to work productivity has a very close and solid relationship. Implication: A hotel dents a competent workforce to work effectively and efficiently to increase its repetitive hotel competitiveness enessinvincibleThee best service certainly requires high employee work productivity. Therefore, the hotel motivates its employees to keep abreast of existing developments and fulfill the wishes and goals of the hotel. Keywords: Motivation, Employee Productivity, Kitchen Employees, Mandarin Oriental Hotel Jakarta.